An unusual case of acute otitis media resulting in Gradenigo syndrome: CT and MRI findings - Juan Quesada, M.D.; Andrew Kong, M.D.; Eliza Tweddle, M.D. (Radiology Case Reports, 2021)
With the widespread use of antibiotics, Gradenigo syndrome is a rare complication of acute otitis media (AOM) and acute mastoiditis. It is an uncommon form of petrous apicitis and can be life-threatening. We report the case of a 14-year-old female with unresolved AOM, who developed otorrhea, ipsilateral headaches, diplopia and raised inflammatory markers. Magnetic Resonance Imaging (MRI) demonstrated features of petrous apicitis and confirmed the suspicion of Gradenigo syndrome. The objective of this clinical case report is to highlight this unusual syndrome together with its radiological appearance to improve its diagnosis and management.